An analytical Study of the Reality of Legal Knowledge of Some Group Games among Physical Education Teachers in Babylon - Saddam Fakhri Barto; Husam Kadhim Jawad; Hayder Jasim Shaalan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The research objectives to identify the level of legal knowledge of physical education teachers in Babylongovernorate, as for the research methodology, the researcher used the descriptive approach in the style ofsurvey studies because it is the best and easiest curriculum to reach the achievement of the objectives to beresearched. The research community of physical education teachers in the Babylon education directoratefor the academic year 2020-2021 has been identified, their number (699) distributed into four departmentseach: From (Al-Hilla Al-Markazi, Al-Mahawil District, Al-Hashemiya District, Al-Musayyib District),as for the research sample, it was determined randomly by (223) teachers and schools, and it formed apercentage of (31,90) of the research community. As for the most important conclusions, they were that thecurrent scale is able to reveal the level of legal knowledge of physical education teachers, as the scale showsthat there is a clear weakness in the legal knowledge of physical education teachers in some group gamesresulting from not following up on the amendments to the law of these games. As for the most importantrecommendations, they were as follows: Paying attention to the law for all games in a more serious mannerby physical education teachers, it is also necessary to give part of the lesson time in which the legal aspect isaddressed and to hold courses or training sessions to explain and interpret the articles of law for some groupgames, and also directing teachers by their supervisors upon their visits to a simplified explanation of thelaw during the implementation of the lesson plan, with the follow-up of sports activity through field visits tofind out the legal level of physical education teachers, especially (female teachers).